El Exploring entrepreneurial orientation in Ecuadorian exporting companies: A PLS-SEM approach - Jean Palomeque-Jaramillo; Emanuel Ferreira-Leite; María José Pérez-Espinoza; Carolina Uzcategui-Sánchez (Sociedad & Tecnología)
This study investigates the impact of Entrepreneurial Orientation (EO) on the strategic performance of small and medium-sized enterprises (SMEs) in El Oro, Ecuador, focusing on the export sector. Utilizing Partial Least Squares Structural Equation Modeling (PLS-SEM), the research analyzes how five dimensions of EO—innovation, risk-taking, proactiveness, competitive aggressiveness, and autonomy—contribute to the operational effectiveness of SMEs engaged in international markets. The analysis highlights that proactiveness and competitive aggressiveness are particularly influential, underscoring their importance in enhancing the strategic posture of SMEs in volatile export environments. Conversely, autonomy shows a more modest impact, suggesting potential external and internal barriers that might curtail strategic independence. The findings elucidate the critical role of specific EO dimensions in promoting adaptability and aggressive market positioning, essential for success in global markets. The study not only provides insights into the dynamics of EO in the Ecuadorian context but also offers practical implications for SMEs aiming to refine their entrepreneurial strategies to better navigate the complexities of international trade.